2006
DOI: 10.1007/s11259-006-3230-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Eprinomectin in Plasma and Milk following Subcutaneous Administration to Lactating Dairy Cattle

Abstract: Eprinomectin is only available as a topically applied anthelmintic for dairy cattle. To determine whether eprinomectin can be applied as an injectable formulation in dairy cattle, a novel injectable formulation was developed and was subcutaneously delivered to four lactating dairy cattle at a dose rate of 0.2 mg/ kg. Plasma and milk samples were collected. The concentrations of eprinomectin in all samples were determined by HPLC. The peak plasma concentration (C(max))of 44.0+/-24.2 ng/ml occurred 39+/-19.3 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
3
18
1
1
Order By: Relevance
“…However, the pour-on formulation is not licensed in China. Instead, an injection formulation of eprinomectin is approved to use in dairy cows in China (Baoliang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the pour-on formulation is not licensed in China. Instead, an injection formulation of eprinomectin is approved to use in dairy cows in China (Baoliang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…From the large number of studies performed in the bodies of hosts, it seems clear that the kinetic behavior of these drugs varies markedly from one molecule to another (Hennessy and Alvinerie, 2002) and seems to be governed by their physicochemical properties such as lipophilicity. The milbemycin moxidectin is characterized by wide distribution in tissues and a remarkable persistence in the organism, whereas avermectins, such as ivermectin and eprinomectin, show lower volumes of distribution and shorter mean residence times (Lanusse et al, 1997;Baoliang et al, 2006). In addition, moxidectin seems to have a different affect on parasites (Prichard and Roulet, 2007), and it has been suggested that it may select less strongly for resistance than ivermectin (Ranjan et al, 2002).…”
mentioning
confidence: 99%
“…In this study, eprinomectin was found to be 100% effective at eliminating adult T. vitulorum infection by single pour-on dose of 0.5 mg/kg administration to calves The pharmacokinetics of eprinomectin in dairy cattle following topical at dose of 0.5 mg/kg (Alvinerie et al 1999) and subcutaneously at dose of 0.2 mg/kg (Baoliang et al 2006) administration have been reported. Alvinerie et al (1999) and Baoliang et al (2006) reported in their studies that the maximum plasma concentration occurred 2.02 days and 39.0±19.3 h post administration, respectively. In this study, T. vitulorum decreased the faeces egg number by (EPG) 58.14% and 97.99% on D2 and D4, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…However, all of them have a milk withdrawal period in cattle (Chicoine et al 2007;Dupuy et al 2008). The major advantage of eprinomectin over other endectocides is the subsequent zero milk withdrawal periods (Alvinerie et al 1999;Baoliang et al 2006).…”
Section: Discussionmentioning
confidence: 99%